Comparison of antidepressant use between adult populations living in urban and rural communities in Israel. (3rd September 2018) - Leventhal Perek, Sharon; Thomas, Katharine; Gaver, Anat; Matalon, Andre; Yeshua, Hanny
Abstract: Background: Depression and anxiety are among the most prevalent disorders in primary care. City dwelling is commonly cited as a risk factor for mental disorders, but epidemiological evidence for this relationship is inconclusive. Objective: To compare the prevalence of antidepressant use, as a proxy for the level of depressive disorders, between patients in Israeli urban and rural communities. Methods: A cross-sectional study, based on data drawn from the registry of the largest health maintenance organization in Israel. The prevalence of antidepressant purchase during 2014 was evaluated for 581291 patients living in urban and rural communities. Data were also collected for potential confounding variables: age, gender, comorbidity, socioeconomic status and being a holocaust survivor. Results: Results showed higher rates of antidepressant use among patients living in urban (11.8%) compared with rural communities (8.1%; <0.001). A particularly high rate of antidepressant use was found on kibbutz (15.9%), a collective rural community in Israel, compared with both urban and other rural communities. Kibbutz compared with other rural communities: odds ratio (OR) = 1.73, P < 0.001; urban communities compared with non-kibbutz rural communities: OR = 1.21, P < 0.001. A significantly lower rate of antidepressant use was found in urban and rural Arab-majority communities (3.9% and 3.8%, respectively). Conclusions: Antidepressant use varies significantly between different communities in Israel. The highest rate of antidepressant use in our study was found on kibbutz, followed by that in urban communities, with the lowest rates in non-kibbutz rural communities. This difference may derive from different depression rates, stigma of mental illness and awareness of mental disorders.